Designable Micro‐/Nano‐Structured Smart Polymeric Materials (Adv. Mater. 46/2022). Issue 46 (17th November 2022) - Wang, Wei; Li, Ping‐Fan; Xie, Rui; Ju, Xiao‐Jie; Liu, Zhuang; Chu, Liang‐Yin
Abstract : Smart Polymeric Materials In article number 2107877, Liang‐Yin Chu and co‐workers review the recent progress of smart polymeric materials that combine micro‐/nanostructures and molecular design to achieve designable advanced functions. The understanding of the interplay between the micro‐/nanostructures and their responsive properties creates new opportunities for exploiting application‐oriented smart materials with desired functions.